Appropriating The Cambridge Platform’s Neo-Congregational Polity - Rutherford, J. Alexander (Ecclesiology, 2025)
This article argues that Baptists can learn, with regard to their practice of governance, from the seventeenth-century Congregational churches of New-England. After showing that The Cambridge Platform of Discipline (1648) offers two accounts of polity, ‘congregational’ and ‘neo-congregational’, it is argued that neo-congregational polity is not only more desirable than congregational polity (as the Platform argued) but offers a more consistent account of biblical ecclesiology. Baptist churches, sharing similar roots and ecclesiology with Congregationalism, stand to benefit from the insights of their seventeenth-century brothers and sisters.